Nitrogen transformations and emission of greenhouse gases from three acid soils of humid tropics amended with N sources and moisture regime. II. Nitrous oxide and methane fluxes - Khalil, M.I.; Boeckx, P.; Rosenani, A.B.; Van Cleemput, O. (Marcel Dekker, 2001)
Potentials of three Malaysian acid soils on nitrous oxide (N2O) and methane (CH4) emission were studied. The soils were incubated during 15 days under two moisture regimes and amended with organic and inorganic nitrogen (N) sources. Soil type, moisture content and NO3- availability influenced the N2O production. Under aerobic conditions, N2O flux was low due to small nitrification and some probable denitrification from the anoxic microsites and the total N2O flux varied from 0.3 to 2.8 mg N2O-N kg-1 soil. Under anaerobic conditions, the total flux ranged from < 0.1 to 87.1 mg N2O-N kg-1 soil. The soil with a higher availability of water-soluble organic carbon (WSOC) emitted the highest N2O while NO3- was not liming, indicating the presence of denitrifiers adjusted to the acid environments. The N2O emission influenced markedly by the addition of sugar beet leaves having low C/N ratio, which was followed by KNO3. Addition of wheat straw having high C/N ratio decreased the amount of mineralized N and consequently decreased the N2O emission. The pH and reducing capacity of the soils was low and hence, CH4 emission remained low even under anaerobic conditions. During the aerobic incubation, the total CH4 flux ranged from 0.4 to 1.3 mg CH4-C kg-1 soil, and the highest being observed from the soil having high WSOC with or without application of NH+4 fertilizer. Under anaerobic conditions, the CH4 emission was slightly higher and total flux varied from 0.7 to 2.0 mg CH4-C kg-1 soil. The pattern of CH4 formation was complex but an influence of mineral N could be observed either in single or in combination with C sources.